Acidity enhancement through synergy of penta- and tetra-coordinated aluminum species in amorphous silica networks - Zichun Wang (Nature Portfolio, 2020)
Increasing the strength of silanols in silica-aluminas can promote their catalytic activity in various applications. Here, the authors present a synergistic effect of two neighboring Al sites on the same silanol group, which can enhance the strength of silanol proton from moderate to zeolitic strength.